Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5758/vsi.2016.32.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Infected Groin (Graft/Patch): Managed with Sartorious Muscle Flap

Abstract: Purpose:The purpose of this study was to review the natural history, clinical outcome and safety in patients undergoing sartorius muscle flap (SMF) for groin infection, including lymphocele.Materials and Methods:We retrospectively reviewed the records of patients who underwent SMF in a single center between 2000 and 2009.Results:Thirty patients (17 male, 13 female) underwent SMF for groin infection, which included infections of 22 artificial femoral bypass grafts (including 2 cryoveins) and 5 common femoral pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Hospital stay and follow-up. Fifteen papers reported on the length of hospitalisation (10,16,17,22,23,27,(32)(33)(34)(35)(36)(37)(38)(39)41). The average hospital stay after the reconstruction was in vivo 33: 1-10 (2019) 2 Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Hospital stay and follow-up. Fifteen papers reported on the length of hospitalisation (10,16,17,22,23,27,(32)(33)(34)(35)(36)(37)(38)(39)41). The average hospital stay after the reconstruction was in vivo 33: 1-10 (2019) 2 Table I.…”
Section: Resultsmentioning
confidence: 99%
“…29 Ryu DY et al mentioned that Sartorius muscle flap lacks bulk and has a limited arc rotation, making it suboptimal for large wounds, in comparison to rectus femoris muscle flap, but the rectus femoris muscle flap needs a longer separate incision in the thigh. 16 They stated also that due to the segmental blood supply arising from superficial femoral artery, some vascular surgeons might hesitate to use the Sartorius muscle flap in patients with an occluded superficial femoral artery. Lastly despite this they concluded that the use of Sartorius muscle flap is recommended to treat groin wound infection, including lymphoceles.…”
Section: Discussionmentioning
confidence: 99%
“…Limb loss and mortality rates were reported as 10% -79% and 9% -58%, respectively. 16 Many of new researches suggest early initiation of targeted anti-microbial therapy and debridement, in conjunction with coverage of the femoral vessels by viable muscle flap, can help in achieving graft and limb salvage. [17][18][19] In 2005 Schutzer R et al recommended the early transposition of the Sartorius muscle for exposed patent infra-inguinal bypass grafts describing it as the viable alternative in the armament of the surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 17 included articles were published between 1994 and 2017. 2,3,9,10,[16][17][18][19][20][21][22][23][24][25][26][27][28] Two studies were case reports 18,19 ; the other 15 were retrospective cohort studies. A summary of the most important study characteristics of the included articles and the methodological scores is provided in Table I.…”
Section: Study Characteristicsmentioning
confidence: 99%